Insulin regulates human pancreatic endocrine cell differentiation in vitro - Perla Cota; Özüm Sehnaz Caliskan; Aimée Bastidas-Ponce; Changying Jing; Jessica Jaki; Lama Saber; Oliver Czarnecki; Damla Taskin; Anna Karolina Blöchinger; Thomas Kurth; Michael Sterr; Ingo Burtscher; et al. (Elsevier, 2024)
Objective: The consequences of mutations in genes associated with monogenic forms of diabetes on human pancreas development cannot be studied in a time-resolved fashion in vivo. More specifically, if recessive mutations in the insulin gene influence human pancreatic endocrine lineage formation is still an unresolved question. Methods: To model the extremely reduced insulin levels in patients with recessive insulin gene mutations, we generated a novel knock-in H2B-Cherry reporter human induced pluripotent stem cell (iPSC) line expressing no insulin upon differentiation to stem cell-derived (SC-) β cells in vitro. Differentiation of iPSCs into the pancreatic and endocrine lineage, combined with immunostaining, Western blotting and proteomics analysis phenotypically characterized the insulin gene deficiency in SC-islets. Furthermore, we leveraged FACS analysis and confocal microscopy to explore the impact of insulin shortage on human endocrine cell induction, composition, differentiation and proliferation. Results: Interestingly, insulin-deficient SC-islets exhibited low insulin receptor (IR) signaling when stimulated with glucose but displayed increased IR sensitivity upon treatment with exogenous insulin. Furthermore, insulin shortage did not alter neurogenin-3 (NGN3)-mediated endocrine lineage induction. Nevertheless, lack of insulin skewed the SC-islet cell composition with an increased number in SC-β cell formation at the expense of SC-α cells. Finally, insulin deficiency reduced the rate of SC-β cell proliferation but had no impact on the expansion of SC-α cells. Conclusions: Using iPSC disease modelling, we provide first evidence of insulin function in human pancreatic endocrine lineage formation. These findings help to better understand the phenotypic impact of recessive insulin gene mutations during pancreas development and shed light on insulin gene function beside its physiological role in blood glucose regulation.